Adaptation and psychometric evaluation of the Stoma‐QOL questionnaire among Chinese rectal cancer patients with colostomy. Issue 4 (10th March 2022) - Shao, Lu; Lv, Lin; Zheng, Mei‐Chun; Huang, Man‐Rong; Zhang, Jun‐E
Abstract: Aim: The purpose of this study was to translate the Stoma‐quality of life into Chinese and evaluate its psychometric properties in Chinese patients. Background: Quality of life is an important issue for patients with colostomy, and its appropriate and precise measurement is beneficial to promoting better care. The Stoma‐quality of life questionnaire has been widely used; however, the validity and reliability of its Chinese version has not been determined. Design: A cross‐sectional validation study was conducted. Methods: We translated the Stoma‐quality of life into Chinese using standardized methods. Then it was psychometrically tested on a convenience sample of 513 patients with colostomy. Construct validity was evaluated via exploratory factor analysis and confirmatory factor analysis. Reliability was measured with Cronbach's alpha and the split‐half Spearman–Brown coefficient. Results: The content validity, the Cronbach's α coefficient and the Spearman–Brown split‐half reliability coefficient indicated adequate validity and reliability. The exploratory factor analysis yielded four common factors, and the cumulative variance contribution rate was 67.5%. Moreover, the confirmatory factor analysis showed a good model fit. Conclusion: This study confirmed that the Chinese version of Stoma‐quality of life is an effective and reliable measurement for evaluating the quality of life of patients with colostomy. Summary statement: What is already known about this topic? Quality of life (QOL) is an important issue for patients with colostomy, and it is conducive to evaluate the effect of specific treatment and nursing interventions. However, a tailored instrument measuring QOL in Chinese patients with colostomy is lacking. The Stoma‐QOL is a widely used stoma‐specific instrument based on Hunt and McKennal's basic QOL demand model and has shown acceptable psychometric properties. What this paper adds? This study provides evidence of the construct validity and internal consistency reliability of the Stoma‐QOL‐C. The four‐factor structure of the scale shows the aspects and complexity of QOL of patients with colostomy. The study proves the Stoma‐QOL‐C a valid and reliable measure of assessing QOL of patients with colostomy. The implication of this paper: The Stoma‐QOL‐C could be used as a disease‐specific scale to evaluate the QOL of patients with colostomy. This study adds the knowledge of the psychometric properties regarding the inventory in diverse cultural backgrounds.